The Linguistic & Scientific Mysteries of Quran (Analysis of Verse 30 Chapter Al-Anbiya in the light of English Quran Translations) - Dr. Shair Ali Khan; Dr. Nargis Nazi (jihat-ul-islam, 2021)
Quran is the book of universal guidance for humanity. It clearly explains somesciences in its discourse, and sometimes it justprovides a hint and a gesture to various sciences. While translating the word of Allah in other languages, translators fail to convey the exact rhetorical and semantic meanings, and stylistical features, and symphonic beauties in the target languages which may cause in the destruction of Allah’s word; its beauty and vastness. Quran is not a book of science, but it contains verses that explain scientific facts and principles. Converting their true meaning in the shape of a faithful translation is a lasting service to humanity. The verse No 30 in chapter Al-Anbiya describes a scientific fact of the birth of this universe in a very symphonic style of word construction. Its translation is miracle from phonetic side and a valuable contribution on the other side for scientists, scholars and students.